2016
DOI: 10.1117/1.jbo.21.6.066003
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic imaging of angiogenesis in a subcutaneous islet transplant site in a murine model

Abstract: , "Photoacoustic imaging of angiogenesis in a subcutaneous islet transplant site in a murine model," J. Biomed. Opt. 21(6), 066003 (2016), doi: 10.1117/1.JBO.21.6.066003. Abstract. Islet transplantation (IT) is an established clinical therapy for select patients with type-1 diabetes. Clinically, the hepatic portal vein serves as the site for IT. Despite numerous advances in clinical IT, limitations remain, including early islet cell loss posttransplant, procedural complications, and the inability to effectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…[72][73][74] However, given the financial cost of lectin and how lectin delivery is traditionally based on body weight, 26 a more cost-effective procedure for large animal models is desired. Photoacoustic imaging, 75 ultrasound imaging, 76,77 and positron emission topography 78 are noninvasive techniques that have been employed for the longitudinal tracking of organ blood flow and angiogenesis in the subcutaneous space of rodents; 79,80 although equipment costs and access, low imaging depth, and low spatial resolution are common constraints. 82 The excellent correlation between our microsphere perfusion data and quantified immunostaining validates the utility of this terminal fluorescent microsphere perfusion technique in the subcutaneous space.…”
Section: Fluorescent Microsphere Perfusion For Porcine Subcutaneous T...mentioning
confidence: 99%
“…[72][73][74] However, given the financial cost of lectin and how lectin delivery is traditionally based on body weight, 26 a more cost-effective procedure for large animal models is desired. Photoacoustic imaging, 75 ultrasound imaging, 76,77 and positron emission topography 78 are noninvasive techniques that have been employed for the longitudinal tracking of organ blood flow and angiogenesis in the subcutaneous space of rodents; 79,80 although equipment costs and access, low imaging depth, and low spatial resolution are common constraints. 82 The excellent correlation between our microsphere perfusion data and quantified immunostaining validates the utility of this terminal fluorescent microsphere perfusion technique in the subcutaneous space.…”
Section: Fluorescent Microsphere Perfusion For Porcine Subcutaneous T...mentioning
confidence: 99%
“…Another minimally invasive and easily accessible area of islet transplantation is the subcutaneous space. Although subcutaneous islet transplant studies commonly involve the study of euglycemia restoration following diabetes induction, this method of transplantation has also been utilized in intravital microscopy studies involving photoacoustic imaging due to proximity to surface ( 24 ). However, to date, this method of imaging has only been used to study transplant revascularization in syngeneic recipient animals ( 24 ).…”
Section: Transplantation Sites For Fluorescent Imaging Purposesmentioning
confidence: 99%
“…Although subcutaneous islet transplant studies commonly involve the study of euglycemia restoration following diabetes induction, this method of transplantation has also been utilized in intravital microscopy studies involving photoacoustic imaging due to proximity to surface ( 24 ). However, to date, this method of imaging has only been used to study transplant revascularization in syngeneic recipient animals ( 24 ). The major drawback of using this site for islet transplantation is the relative avascularity of this environment compared to other transplantation sites discussed above.…”
Section: Transplantation Sites For Fluorescent Imaging Purposesmentioning
confidence: 99%
See 1 more Smart Citation
“…Shi et al reported that PI can be used to track angiogenesis at a subcutaneous islet transplant site in a mouse model. 76 PI employed in this study may be used for tracking angiogenesis of transplanted islets.
Figure 3 Trimodal imaging of transplanted pancreatic islets in scaffolds.
…”
Section: Bioluminescence Imaging (Bli)mentioning
confidence: 99%